2020
DOI: 10.1055/s-0040-1702260
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Comparison of Modes of Failures among Titanium and One- and Two-piece Zirconia Abutment under Static Load

Abstract: ObjectivesThe objective was to assess modes of failures under static load (SL) among titanium (Ti) and one-and two-piece zirconia abutment (ZA) in vitro. Materials and MethodsThe Ti abutments were digitally scanned for the fabrication of the one-and two-piece zirconia abutment specimens. This was done to standardize the design of the one-piece abutment and make it the blueprint of the Ti abutment. Twenty-one implant abutments and 21 implant replicas were categorized into three groups as follows: group 1 (Titan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
0
6
0
1
Order By: Relevance
“…However, in the present study, the risk of complication in hybrid‐abutment‐crown and screw was high in Ti‐Hybrid. Similarly, previous studies showed that the typical failure mode of titanium abutment was screw fracture, screw bending, and abutment bending 40,41 …”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…However, in the present study, the risk of complication in hybrid‐abutment‐crown and screw was high in Ti‐Hybrid. Similarly, previous studies showed that the typical failure mode of titanium abutment was screw fracture, screw bending, and abutment bending 40,41 …”
Section: Discussionmentioning
confidence: 72%
“…Interestingly, the Ti‐base, which was designed as the stress absorber, can improve stress distribution at the implant‐bone interface, decrease implant deformation risk, and secure peri‐implant bone loss 5,15 . It had been shown that the typical failure mode of Ti was screw fracture and abutment bending, while the typical failure mode of Zir‐TiBase was screw bending and abutment fracture 40,41 . Consequently, the complication risk of screw loosening and bending in Zir‐TiBase must be observed cautiously.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In vitro studies, whether simplified or with complex approaches add to our understanding of the properties and mechanical behavior of dental materials and restorations. 1 2 Two different approaches of in vitro studies can be identified in the literature; studies aim at measuring physical and mechanical properties, and studies aim to simulate clinical behavior. 3 Although the first approach is important in providing information about material properties, estimating failure risk and comparing material variants, 4 it is known clinically that failures of all-ceramic restorations are a complex process which occur mostly as a result of fatigue stresses in challenging oral conditions.…”
Section: Introductionmentioning
confidence: 99%